2010
DOI: 10.1108/13552511011084553
|View full text |Cite
|
Sign up to set email alerts
|

Optimal redundancy allocation in complex systems

Abstract: PurposeThis paper aims to focus on solving highly constrained redundancy optimization problems in binary complex systems.Design/methodology/approachThe proposed algorithm searches a possibly improved solution in the k‐neighborhood (k≥2) of the current best feasible solution, by adding one unit in a selected subsystem and eliminating one from some other subsystem(s).FindingsThe algorithm is tested on complex system structures from the literature by solving a set of problems (with both linear and non‐linear cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Performance(84) EXACT PROBLEM-SPECIFIC(3) [1], [112], [126], EXACT STANDARD(14) [12]- [15], [42]- [44], [69], [117], [169], [174], [218], [236], [241], GENERAL(1) [153], METAHEURIS-TIC(45) [2], [3], [23], [29], [32], [35], [38]- [40], [45], [46], [66], [73], [77], [83], [84], [88], [114], [122]- [124], [130], [133], [141], [143], [145], [160], [161], [170], [175]- [177], [188], [189], [196]- [198], [200], [220], …”
Section: Qa Optimization Strategy Type Constraint Handlingmentioning
confidence: 99%
“…Performance(84) EXACT PROBLEM-SPECIFIC(3) [1], [112], [126], EXACT STANDARD(14) [12]- [15], [42]- [44], [69], [117], [169], [174], [218], [236], [241], GENERAL(1) [153], METAHEURIS-TIC(45) [2], [3], [23], [29], [32], [35], [38]- [40], [45], [46], [66], [73], [77], [83], [84], [88], [114], [122]- [124], [130], [133], [141], [143], [145], [160], [161], [170], [175]- [177], [188], [189], [196]- [198], [200], [220], …”
Section: Qa Optimization Strategy Type Constraint Handlingmentioning
confidence: 99%
“…Tian and Zuo (2008) presented a model for a multi-state seriesparallel system to jointly determine the optimal component state distribution and optimal redundancy for each stage. Kumar et al (2010) and Agarwal et al (2010) presented new heuristic methods for solving constrained RAPs in varied complex systems, such as computer networks, communication systems, transportation systems, etc. To address the uncertainty factor in the field of reliability-based design optimisation, Robert and Stephen (2009) presented a decision-analytic approach, an alternative to chance constrained approach, to optimise an objective function subject to uncertainties about design constraints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agarwal and Aggarwal 16 showed that their algorithms perform better than those in Kohda and Inoue and Shi 18,19 and provide attractive alternatives to that of Kim and Yum. 20 Recently, Aggarwal 30 proposed a heuristic algorithm based on 3-neighborhood, which is an improvement over Agarwal et al 25…”
Section: Introductionmentioning
confidence: 99%
“…A huge number of techniques, including heuristic and metaheuristic, have been developed for solving redundancy allocation problems for complex systems in the literature. 16,[18][19][20][21][22][23][24][25][26][27][28][29][30] Shi 19 proposed a heuristic algorithm to solve problems of redundancy allocation based on minimal path sets. Here, the feasible solutions obtained in successive iterations are in 1-neighborhood or 2-neighborhoods of each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation